Cutting Ice with High Pressure Water Jets (Decoupage de la Glace par de Puissants Jets D'eau). - Coveney,D B (1981)
The potential of high pressure water jets to cut slots in an ice sheet, primarily for possible use as an assist to ice breaking, has been under investigation. In the field, slots have been cut into and through fresh water ice, about 0.7 m thick with water jets applying up to about 260 kW of power to the ice. This report describes the ice cutting performance of small to moderate scale water jets. The majority of cuts produced a narrow, clean kerf, indicative of erosion in a ductile material, while other cuts produced a wide spalled trench, indicative of spalling in a brittle material. Still others produced a combination of the two modes of cutting, with a wide, shallow trench and a narrow, deep kerf below the trench. In many cases the ice was also crazed extensively by the water jet. The causes and the effects of these characteristics on ice cutting performance are discussed, along with the effects of jet traverse speed, nozzle diameter, nozzle pressure, nozzle standoff, ice characteristics and the overall scale of the system. An empirical relationship, derived by regression analysis, is presented correlating the jet penetration to the power in the jet, the jet traverse speed, the nozzle stand-off and the estimated ice temperature. Summary in French.